Kuat Geser Tanah Gambut Berserat di Kabupaten Ogan Ilir - Hartini Hartini; Yulindasari Sutejo; Febrian Hadinata (Syntax Corporation, 2022)
The peat soil used in this research is fibrous peat soil. The block sampling method was carried out to obtain undisturbed soil samples. The sample locations are from Tanjung Pule Village and Bakung Village, Ogan Ilir Regency. The property index and classification tests include: water content (w), specific gravity (Gs), acidity (pH), ash content (AC), organic content (OC), and fiber content (FC). The parameters of the peat soil shear strength were obtained from the Triaxial UU and Vane Shear tests. Test results in Bakung Village: 693.14 %, Gs = 1.79, pH = 3.01, e = 9.95, b = 12.74 kN/m3, d = 1.61 kN/ m3 OC = 96.60%, AC = 3.3%, and FC = 27.14 %. Test results in Tanjung Pule Village: = 714,77 %, Gs = 1,72, pH = 4,14, e = 13,06, gb = 9,78 kN/m3, gd = 1,11kN/m3, OC = 93.00 %, AC = 7 %, and FC = 36.35 %. Fiber content (FC) in Bakung and Tanjung Pule villages is > 20 %, so it is classified as fibrous peat soil. Triaxial test results obtained shear strength values ​​t =10.72 kPa (Bakung Village) and t =11.62 kPa (Tanjung Pule Village). While the results of the Vane Shear test in Bakung Village, Su = 11.39 kPa and Tanjung Pule Village, Su = 14.31 kPa. Keywords: Peat Soil, Shear Strength, Triaxial, Vane Shear